2015
DOI: 10.1002/anie.201504007
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II)‐Catalyzed Allylic CH Oxidation of Hindered Substrates Featuring Tunable Selectivity Over Extent of Oxidation

Abstract: The use of Oxone and a palladium(II) catalyst enables the efficient allylic CH oxidation of sterically hindered α‐quaternary lactams which are unreactive under known conditions for similar transformations. This simple, safe, and effective system for CH activation allows for unusual tunable selectivity between a two‐electron oxidation to the allylic acetates and a four‐electron oxidation to the corresponding enals, with the dominant product depending on the presence or absence of water. The versatile syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…The other is an oxygenative allylic transposition that involves a migration of the alkene functionality of 1 to give regioisomeric enone 2 (Scheme b). To the best of our knowledge, a sequence of an ene reaction of an alkene and singlet oxygen (Schenck ene reaction) and subsequent acetylation–dehydroacetoxylation of the resulting allyl hydroperoxide is the only known single‐step method for this transformation . Although some successful applications of this method to the synthesis of complex molecules have been demonstrated, this method has some major drawbacks: it is potentially dangerous due to the explosive nature of the hydroperoxide intermediate, it gives modest yields of enones from trisubstituted alkenes due to poor regioselectivity of the singlet oxygen ene reaction, and it is generally not applicable to trans ‐disubstituted alkenes due to lack of the reactivity of singlet oxygen toward them .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The other is an oxygenative allylic transposition that involves a migration of the alkene functionality of 1 to give regioisomeric enone 2 (Scheme b). To the best of our knowledge, a sequence of an ene reaction of an alkene and singlet oxygen (Schenck ene reaction) and subsequent acetylation–dehydroacetoxylation of the resulting allyl hydroperoxide is the only known single‐step method for this transformation . Although some successful applications of this method to the synthesis of complex molecules have been demonstrated, this method has some major drawbacks: it is potentially dangerous due to the explosive nature of the hydroperoxide intermediate, it gives modest yields of enones from trisubstituted alkenes due to poor regioselectivity of the singlet oxygen ene reaction, and it is generally not applicable to trans ‐disubstituted alkenes due to lack of the reactivity of singlet oxygen toward them .…”
Section: Methodsmentioning
confidence: 99%
“…One is ad irect oxygenation at the allylic positiono fa lkene substrate 1 to give enone 2' ("normal" allylic oxygenation,S cheme 1a). [4] Althoughs ome successful applicationso ft his methodt ot he synthesis of complex molecules have been demonstrated, [5] this methodh as some major drawbacks:i ti sp otentially dan-gerousd ue to the explosive nature of the hydroperoxide intermediate, it gives modest yields of enones from trisubstituted alkenesd ue to poor regioselectivity of the singlet oxygen ene reaction, and it is generally not applicable to trans-disubstituted alkenes due to lack of the reactivity of singlet oxygen toward them. [2d] The other is an oxygenativea llylic transposition that involves am igration of the alkene functionality of 1 to give regioisomeric enone 2 (Scheme 1b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 We found that reactions of acyclic ketones 1a and 1b occurred to full conversion in 10 h, despite the difference in the steric properties of the quaternary centers in these two ketones. Cyclic ketones containing 5-, 6-, and 7-membered rings underwent oxidation in high yields in 15 h ( 1c , 1d , 1e ).…”
mentioning
confidence: 69%
“…[23][24][25][26] Some alternative processes usually based on the acetoxylation of alkenes or related compounds have also been developed. [27][28][29][30][31] To this end, the arylation of dienes/allenes with concomitant acetoxylation promoted by Pd-complexes as a way to produce substituted allyl acetates, Scheme 1, was recently reported. 32,33 1336 S I M I Ć et al…”
Section: Introductionmentioning
confidence: 99%